Pseudoarthrosis treatment with stem cells: an integrative review - De Marco, Luciana Fontes; Dias, Ana Fabricia Feitosa; Vasconcelos, Manuel Fernando Colares De Souza; Pagotti, Lucas Viana; Oliveira, Raphael Andrade; Junior, Odair Sebastião Barboza Da Silva (Journal of the Foot & Ankle, 2024)
Objective: This integrative review aims to synthesize and critically analyze the current literature on the use of stem cells in the treatment of pseudarthrosis. Methods: A systematic search was conducted in electronic databases, resulting in the inclusion of preclinical and clinical studies that investigated the impact of stem cells on bone healing. Results: Proposed biological mechanisms include the ability of stem cells to promote osteogenic differentiation and secrete growth factors that facilitate tissue repair. Results indicate that stem cell treatment often increases rates of successful bone healing, improving functional outcomes and reducing postoperative complications. Limitations include the heterogeneity in treatment protocols and the need for randomized clinical trials to robustly validate these findings. Conclusion: The use of stem cells emerges as a promising approach in the management of pseudarthrosis, promoting a new perspective in orthopedic regenerative medicine. Level of evidence V; Expert Opinion.